(untitled) (Scientific journal of the Fergana State University, 2024)
In today’s changing world, the leading goal of teaching a foreign language is the formation of communicative competence, including linguistic, socio-cultural, educational, cognitive and compensatory competencies. In the process of communicative learning, self-esteem and self-control of students are of particular importance. The language portfolio effectively contributes to the formation of the necessary skills of reflection and evaluation of the results of cognitive activity. The portfolio is one of the most modern and promising innovative tools and is used as a means of reflecting students’ achievements in language acquisition based on literary texts.